Mental Health in the Covid-19 Pandemic: Impact and Global Recovery Strategy Literature Review - Itha Puspita Sari; Nurlaela Nurlaela; Ani Maryani; Ahmad Yani (Jurnal Indonesia Sosial Sains, 2025)
The COVID-19 pandemic has significantly affected the mental health of people worldwide, including in Indonesia. The surge in mental disorders such as depression, anxiety, stress, and trauma highlights that this crisis impacts both physical and psychological well-being. This study aims to examine the mental health impact and global recovery strategies through a literature review approach. The method used involved reviewing literature from reputable databases such as PubMed, Science Direct, and Google Scholar, resulting in 10 selected articles that met the inclusion criteria. Findings reveal that vulnerable groups, including healthcare workers, the elderly, and individuals with pre-existing mental disorders, were more severely impacted. The study emphasizes the need for responsive mental health systems, long-term investment, and social stigma reduction. Recovery efforts include raising awareness, expanding access to services, and community-based support. These findings provide a comprehensive understanding of mental health challenges during the pandemic and underscore the importance of a holistic and sustainable response.